Contribution of the Centrifugal Partition Chromatography (CPC) to the Purification of Zincke Reaction Products. Issue 12 (28th March 2019) - Lachaise, Isabelle; Zeghbib, Narimane; Asskar, Ghada; Rivard, Michael; Martens, Thierry
Abstract: The Zincke reaction poses a difficulty when attempting to purify the crude mixtures and isolate reaction products in analytically pure form. This paper introduces the successful method of using the centrifugal partition chromatography (CPC) to isolate pyridinium salts garnered by this reaction returning good yields and high degrees of purity. Efficient purifications were obtained by using ( n ‐BuOH/MeOH/H2 O) biphasic solvent systems. The CPC confirmed its suitability for isolating compounds prone to decompose during purification on solid stationary phases. It has also proved to be an efficient method for valorizing incomplete Zincke reactions. Abstract : Centrifugal Partition Chromatography (CPC) proved to be an efficient method to isolate pyridinium salts prepared by Zincke reaction with a high degree of purity, even in the case of incomplete conversions where the expected salt is obtained in mixture with unreacted Zincke salt, which is the reagent of the reaction but also a pyridinium salt.